The Role of Promotion and Tourism Activities in Strengthening the Community Economy: Case Study of Lake Shuji - Mutiara Salsabila; Hadi Jauhari; Yulia Pebrianti (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: Tourism holds great potential for enhancing community economic growth, especially in rural areas. This study aims to analyze the influence of tourism promotion and tourism activities on the economic well-being of communities around Danau Shuji, Lembak Village, Muara Enim Regency. Method: A quantitative method with multiple linear regression analysis was used, based on data from 98 purposively selected respondents. The results show that both promotion and tourism activities significantly influence economic well-being (R² = 0.536). Result: This study concludes that community-based tourism development requires the strengthening of digital promotion, diversification of attractions, and inclusive institutions to ensure long-term economic and social benefits. Contribution: Partially, tourism activities had a greater impact than promotion. Tourism activities have created new income sources, opened job opportunities, and encouraged the growth of local MSMEs. In addition to economic impact, community participation in tourism also fosters social transformation, including the increasing involvement of youth and women.